Ação TECNEP: movimentos, mediações e implementação da política de inclusão no IFFar, campus São Vicente do Sul - Gonçalves, Lizandra Falcão (2017)
The research is linked to the area of professional and technological education, developed under the Postgraduate Program in Professional and Technological Education of the Industrial Technical School/UFSM, composing the studies carried out in Research Line 1: Policies and Management in Professional and Technological Education. This study, was based on, issues raised at the meetings of the UFSM Accessibility Commission, which led to the reflection on the inclusion process in Professional and Technological Education. Thus, this research has as its theme the implementation of the public policy Action TECNEP, aimed at the inclusion of people with special educational needs in Professional and Technological Education (EPT). The problematization relates to what movements and experiences were developed when implementing the aforementioned action at the Federal Institute Farroupilha, at the São Vicente do Sul campus. The general objective was to analyze the movements of the TECNEP Action, in order to identify the actions implemented in the studied context. The specific objectives were to investigate the historicity of the TECNEP Action in the context of the campus; Analyze the conditions of inclusion, permanence and completion of students with special educational needs; And understand the limits and possibilities of the TECNEP Action in the context of that campus. Research of theoretical references on public policies, inclusion and professional and technological education, as well as a documentary research in the political landmarks of inclusion in documents related to the TECNEP Action policy. The chosen methodology consists of qualitative research, in the perspective of historical and dialectical materialism. The campus was investigated through a semi structured interview, directed to servers and students with special educational needs, and registered in the field record book. The categories of the method that allowed the analysis of the phenomenon were: historicity, mediation, totality and contradiction. As a result, there is the understanding that the implementation movements of the TECNEP Action at the São Vicente do Sul campus have had significant implications for the institution. The historicity of the implementation of public policy, was evidenced, at the local level in the movements of the actions and implementing experiences, presenting the beginning, apex and decline. Analyzes of the pillars of inclusion, permanence, and conclusion show that they were fulfilled. Understanding the limits and possibilities of politics reveals its decline as an organization, however, this study considers that, at the local level, educational inclusion remains in motion, as it is based on, and manifests itself in the institution's current inclusion policy, opening itself up to many possibilities. Thus, it can be concluded that the experiences of implementing the TECNEP Action policy can contribute to the implementation of other inclusion policies.